Advertising in Social Media Based on Islamic Business Ethics And its Influence on Purchase Decisions (Case Study Gallery Elzatta Kudaile Slawi) - ahmad faqih udin (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The background of this research is the rise of the business world in the global era. The more new business openings, the tighter the competition will be. In order for companies to be able to introduce their products to the market, it is necessary to do marketing through advertising activities. This is like what Gallery Elzatta Kudaile Slawi has done.Of the many existing advertising activities, it must be adapted to business ethics in Islam so as not to disappoint consumers. So based on the background above, the research that you want to study is: 1) What are the advertising strategies that are adapted to Islamic business ethics? (2) How do Gallery Elzatta Kudaile Slawi's advertisements influence purchasing decisions? (3) To what extent do Gallery Elzatta Kudaile Slawi's advertisements affect purchasing decisions?This research consists of Advertising Variables (X) and Purchasing Decision Variables (Y). This research is included in the category of correlational study with a quantitative approach. Intake of research subjects using cluster random sampling technique, namely as many as 83 consumers of Gallery Elzatta Kudaile Slawi. For data collection techniques, researchers used interviews, questionnaires, observation and documentation. While the data analysis technique uses the classic assumption test -normality test and hypothesis testing in the form of simultaneous F test, Coefficient of Determination test (R2), and Partial t test.Based on the results of the analysis of the data obtained, it is known that there is an influence from the advertising activities carried out by Gallery Elzatta Kudaile Slawi on consumer purchasing decisions, so that consumers are interested in buying products at the Elzatta Kudaile Slawi GalleryOf the many existing advertising activities, it must be adapted to business ethics in Islam so as not to disappoint consumers. So based on the background above, the research that you want to study is: 1) What are the advertising strategies that are adapted to Islamic business ethics? (2) How do Gallery Elzatta Kudaile Slawi's advertisements influence purchasing decisions? (3) To what extent do Gallery Elzatta Kudaile Slawi's advertisements affect purchasing decisions?Â This research consists of Advertising Variables (X) and Purchasing Decision Variables (Y). This research is included in the category of correlational study with a quantitative approach. Intake of research subjects using cluster random sampling technique, namely as many as 83 consumers of Gallery Elzatta Kudaile Slawi. For data collection techniques, researchers used interviews, questionnaires, observation and documentation. While the data analysis technique uses the classic assumption test -normality test and hypothesis testing in the form of simultaneous F test, Coefficient of Determination test (R2), and Partial t test.Based on the results of the analysis of the data obtained, it is known that there is an influence from the advertising activities carried out by Gallery Elzatta Kudaile Slawi on consumer purchasing decisions, so that consumers are interested in buying products at the Elzatta Kudaile Slawi Gallery.Keywords: Advertising, Islamic Business Ethics, and Purchasing Decisions